Action presidents. #3, Theodore Roosevelt! - Van Lente, Fred (Van Lente, Fred. Action presidents, 2020)
Proffers a humorous graphic novel presenting historical stories about Theodore Roosevelt, such as the fact that he was made fun of for wearing glasses, wrote books, and gave a speech with a gunshot wound in his chest.